2016
DOI: 10.1177/0022034516678169
|View full text |Cite
|
Sign up to set email alerts
|

The Salivary Microbiome and Oral Cancer Risk: A Pilot Study in Fanconi Anemia

Abstract: Fanconi anemia (FA) is a rare genetic disease characterized by chromosomal instability and impaired DNA damage repair. FA patients develop oral squamous cell carcinoma (OSCC) earlier and more frequently than the general population, especially after hematopoietic stem cell transplantation (HSCT). Although evidence of an etiological role of the local microbiome and carcinogenesis has been mounting, no information exists regarding the oral microbiome of FA patients. The aim of this study was to explore the saliva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…In addition, the genus Streptococcus exhibited moderate classification potential. While normally harmless, these two genera ( Staphylococcus and Streptococcus ) are being growingly investigated in relationship to the development of cancer in different organ sites . These studies have shown conflicting descriptions of these colonizers in carcinogenesis.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In addition, the genus Streptococcus exhibited moderate classification potential. While normally harmless, these two genera ( Staphylococcus and Streptococcus ) are being growingly investigated in relationship to the development of cancer in different organ sites . These studies have shown conflicting descriptions of these colonizers in carcinogenesis.…”
Section: Discussionmentioning
confidence: 55%
“…While normally harmless, these two genera (Staphylococcus and Streptococcus) are being growingly investigated in relationship to the development of cancer in different organ sites. 18,[37][38][39][40][41][42][43] These studies have shown conflicting descriptions of these colonizers in carcinogenesis. Hosgood et al 18 reported enrichment of Streptococcus in lung cancer cases, consistent with our own findings, while Staphylococcus showed no significant differences between cases and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, recent work has highlighted the critical role of metabolic products from specific gut microbiota such as lactobacilli in priming IL-22 dependent mucosal immune responses by innate lymphoid cells via the aryl hydrocarbon receptor, which is fundamental for protection against uncontrolled local Candida expansion [41]. Further, a shift in salivary microbiota has been linked to the risk of oral cancer in selected groups of patients [42]. We found significantly increased abundance of streptococci in APS-1 saliva compared to healthy controls and several streptococci were among the most abundant species in APS-1 saliva.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of HNSCC increases with age, but compared with the general population, patients with FA develop these tumors at much earlier ages, with a median age at diagnosis in the early 30s. Many hypotheses, including human papillomavirus infection, exposure to aldehydes, and chronic infections, have been investigated. However, to the best of our knowledge, the rationale for the 500‐fold to 700‐fold elevated risk of HNSCC in the FA population still has yet to be identified.…”
Section: Introductionmentioning
confidence: 99%